A Fuzzy Logic Control Strategy for Buck PFC Converter Based 4- Switch VSI Fed BLDC Motor Drive - V. Ramesh; Y. Kusuma Latha (Institute of Advanced Engineering and Science, 2016)
In this paper, a new Buck PFC dc–dc converter topology along with fuzzy logic control for a permanent magnet (PM) brushless dc motor (PMBLDCM) has been proposed. The proposed buck-PFC converter topology is on single stage power factor correction converter. A concept of dc link voltage control which is proportional to speed of the PMBLDCM is used in this paper. The stator currents of the PMBLDCM during step change in the reference speed are controlled within the specified limits by an addition of a rate limiter in the reference dc link voltage. The effectives of the proposed control strategy of PMBLDCM drive is validated through simulation results.